Bioactive Properties of Eremostachys macrophylla Montbr. & Auch. Rhizomes Growing in Iran - Parina Asgharian, Abbas Delazar, Farzaneh Lotfipour. Solmaz Asnaashari (Tabriz University of Medical Sciences, 2017)
Background: The current study was assigned to evaluate the antioxidant, general toxicity, anti-proliferative and antimicrobial activities of different extracts obtained from rhizomes of Eremostachys macrophylla (Lamiaceae). Methods: All activities were evaluated by obtaining extracts of E. macrophylla in n-hexane, DCM (dichloromethane) and MeOH (methanol) by soxhlet apparatus. The antioxidant activity of the extracts was evaluated in terms of FRST (free radical scavenging activity test) by DPPH (2, 2-diphenyl-1-picrylhydrazyl). BSLT (Brine shrimp lethality tests), MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide) assay and disc diffusion method were carried out to determine the general toxicity, anti-proliferative and antibacterial activities of the different extracts, respectively. Results: The findings of the study for antioxidant, anti-proliferative and antibacterial effects showed that DCM extract was the most active fraction, but n-hexane extract indicated the most potent effect against Artemia salina. Conclusion: The results revealed strong bioactive effects of nonpolar fractions of E. macrophylla rhizomes. Thus, it is possible to suggest some new potential antioxidant, cytotoxic and antibacterial agents with no harmful effects on noncancerous cells.